Treatment Of Patients with Chronic Coronary Heart Disease of The Elderly And Senile Age With The Help Of High-Tech Methods - I.R. Aghababyan; S.Sh. Joniev; F. A. Jumaev; F. Safarov; I. Daminov (Genius Journals, 2023)
Coronary artery disease (CHD) remains the leading cause of death in elderly patients. Recently, centers for revascularization therapy have been opened in almost all regions of our country. In particular, percutaneous coronary interventions (PCI) are used to effectively manage patients with ACS and PICS to improve the quality of life. These socalled endovascular interventions are currently a highly effective treatment method that can significantly improve the condition of patients and increase their tolerance to physical activity, return people to normal everyday life. In this article, a retrospective analysis was made of elderly and senile patients who underwent percutaneous coronary intervention with various types of stenting. The analysis revealed that the majority of patients were diagnosed with ACS. More than 337 endovascular interventions were performed in 163 patients
Keywords: percutaneous coronary intervention; stenting